Can pancreatic cancer behavior be predicted based on computed tomography measurements of fat and muscle mass?. Issue 2 (December 2016) - Clark, Whalen; Swaid, Forat; Luberice, Kenneth; Bowman, Ty A.; Downs, Darrell; Ross, Sharona B.; Rosemurgy, Alexander S.
Abstract : Introduction: Many studies purport that obesity, and specifically visceral fat, impact survival after pancreaticoduodenectomy for pancreatic adenocarcinoma. However, these studies involve crude measures of obesity [eg, body mass index (BMI)] or visceral fat [eg, linear measurements on computed tomographic (CT) scans]. Some studies purport that weight loss and muscle wasting (ie, sarcopenia) presage poor survival in these patients. This study was undertaken to accurately measure and reexamine the impact of visceral fat, subcutaneous fat, and sarcopenia on pancreatic cancer. Materials and methods: CT scans of 100 patients undergoing pancreaticoduodenectomy for pancreatic adenocarcinoma were reviewed using specialized software to precisely determine the cross-sectional area (CSA) of subcutaneous fat, visceral fat, and psoas muscles at the level of L5 vertebra. In addition, linear measurements of subcutaneous fat and visceral fat were undertaken. Measures of cancer progression included tumor (T) status, nodal (N) status, American Joint Committee on Cancer stage, and overall survival after resection. Regression analysis was utilized, with and without standardization of all measurements to body size. Median data are presented. Results: The median patient age was 67 years, with a BMI of 24 kg/m 2 . Cancer stage was IIB for 60% of patients. BMI, CSA of visceral fat, CSA for subcutaneous fat, CSA for psoas muscles, and linear measurements of visceral and subcutaneous fat were not significantly related to any measures of cancer progression or survival. Standardization to body size did not demonstrate any relationships with cancer progression or survival. Conclusions: Precise and reproducible measures of visceral fat, subcutaneous fat, and muscle mass, even when standardized to body size, do not predict cancer progression or survival in patients undergoing pancreaticoduodenectomy for pancreatic adenocarcinoma. Pancreatic cancer biology and behavior is too complex to predict with a CT scanner. The main focus of pancreatic cancer research should continue to be at the molecular, genetic, and immunologic levels.